Sources : notable selections in marriage and the family - Campo, Diana S. del; Campo, Robert L. del (Connecticut : Dushkin, 1999)
Contenido: Marriage uses to be an institution for the physical survival and well-being of two people and their offspring. Today we have primarily the struggle for psychological and emotional survival. But so far, the changes in the structure, form, and processes of marriage have been too few and too unsystematic to cope with the new psychological and emotional problems.